The effect of artificial anal band on quality of life of patients with fecal incontinence (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate incontinence levels before and after implantation of an artificial anal band (AAB), and to evaluate the change in quality of life of patients with fecal incontinence. Material and Methods: Patients with fecal incontinence who underwent AAB implantation were included in the study. The Cleaveland Clinic/Wexner Incontinence Score (CCIS) and Fecal Incontinence Quality of Life (FIQoL) scales were evaluated before, 2 weeks and 5 years post-implantation.Results: Eight patients underwent AAB implantation. The mean±SD pre-operative CCIS decreased significantly (p0.001) from 19.4±0.5 to 3.1±0.6 two weeks after AAB activation. Similarly, a significant improvement was observed between mean pre- and post-operative FIQoL scores (49.4 vs. 102.0; p=0.012). Most (62.5%) of the patients could actively use the implant. Surgical revision was performed in the post-operative period in 50% of the patients (n=4, 3 women). In 2 (25%) patients, AAB was explanted either due to a secondary surgical site infection (n=1, man) or due to a perianal skin maceration (n=1, man). Conclusion: AAB implantation is an effective treatment option for improving quality of life in patients with fecal incontinence. Appropriate patient selection criteria may improve explantation and surgical revision rates and increase the rate of effective use of AAB. Keywords: Fecal; incontinence; artificial anal band; efficacy; quality of life.
Keywords: Fecal; incontinence; artificial anal band; efficacy; quality of life.